Adiponectin Regulates the Polarization and Function of Microglia via PPAR-γ Signaling Under Amyloid β Toxicity - Song, Juhyun; Choi, Seong-Min; Kim, Byeong C. (Frontiers in Cellular Neuroscience, 2017)
Alzheimer's disease (AD), characterized by the abnormal accumulation of amyloid beta (Aβ), is gradually increasing globally. Given that AD is considered a neuroinflammatory disease, recent studies have focused on the cellular mechanisms in brain inflammatory conditions that underlie AD neuropathology. Microglia are macrophage cells in the central nervous system that are activated in response to Aβ condition. The function of microglia contributes to the neuroinflammation in AD brain, suggesting that microglia regulate the production of inflammatory mediators and contribute to the regeneration of damaged tissues. Adiponectin, an adipokine derived from adipose tissue, has been known to regulate inflammation and control macrophages during oxidative stress conditions. In present study, we investigated whether adiponectin influences the polarization and function of microglia under Aβ toxicity by examining alterations of BV2 microglia function and polarization by Acrp30 (a globular form of adiponectin) treatment using reverse transcription PCR, western blotting, and immunofluorescence staining. Acrp30 promoted the induction of the M2 phenotype, and regulated the inflammatory responses through peroxisome proliferator-activated receptor (PPAR)-γ signaling under Aβ toxicity. In addition, Acrp30 boosted the capacity of Aβ scavenging in microglia. Taken together, we suggest that adiponectin may control the function of microglia by promoting anti-inflammatory responses through PPAR- γ signaling. Hence, we conclude that adiponectin may act as a critical controller of microglia function in the AD brain.